Nujna medicinska služba na stopnji 1a - Kersnik, Janko (Medicinski razgledi, 1997)
In medical circles of Slovenia, emergency medical services are regarded as services provided exclusively by health care professionals. This concept, which excludes any participation of lay public and lay institutions, is not inaccordance with recommendations of Council of Europe. The presented case illustrates the importance of considering emergency medical service as common responsibility of all the people involved.
Keywords: Emergency medical services; nujna medicinska pomoč; Organization and administration; Slovenia; Slovenija; Rescue work; Consciousness disorders